Metabolite profiling of non‐sterile rhizosphere soil. (31st August 2017) - Pétriacq, Pierre; Williams, Alex; Cotton, Anne; McFarlane, Alexander E.; Rolfe, Stephen A.; Ton, Jurriaan
Summary: Rhizosphere chemistry is the sum of root exudation chemicals, their breakdown products and the microbial products of soil‐derived chemicals. To date, most studies about root exudation chemistry are based on sterile cultivation systems, which limits the discovery of microbial breakdown products that act as semiochemicals and shape microbial rhizosphere communities. Here, we present a method for untargeted metabolic profiling of non‐sterile rhizosphere soil. We have developed an experimental growth system that enables the collection and analysis of rhizosphere chemicals from different plant species. High‐throughput sequencing of 16S rRNA genes demonstrated that plants in the growth system support a microbial rhizosphere effect. To collect a range of (a)polar chemicals from the system, we developed extraction methods that do not cause detectable damage to root cells or soil‐inhabiting microbes, thus preventing contamination with cellular metabolites. Untargeted metabolite profiling by UPLC‐Q‐TOF mass spectrometry, followed by uni‐ and multivariate statistical analyses, identified a wide range of secondary metabolites that are enriched in plant‐containing soil, compared with control soil without roots. We show that the method is suitable for profiling the rhizosphere chemistry of Zea mays (maize) in agricultural soil, thereby demonstrating the applicability to different plant–soil combinations. Our study provides a robust method for the comprehensive metabolite profiling of non‐sterile rhizosphere soil, which represents a technical advance towards the establishment of causal relationships between the chemistry and microbial composition of the rhizosphere. Significance Statement: Multitrophic interactions in the rhizosphere are critical for plant growth and health, and are influenced by root exudates and their microbial breakdown products. In this study, we describe a straightforward method for metabolic profiling of non‐sterile rhizosphere soil, which represents an efficient technique to identify novel semiochemicals that shape the microbial community structure and activity of the rhizosphere.